Penerapan Pembiayaan Musyarakah Pada BMT Dana Barokah Muntilan - Shinta Amelia Kurniasari; Risma Wira Bharata (JAS (Jurnal Akuntansi Syariah), 2020)
This study aims to determine the implementation of profit sharing based musyarakah contracts, financing products and financing mechanisms at the Baitul Maal wa Tamwil (BMT) Dana Barokah. This study uses a qualitative method with a case study approach. The data used in the study used primary data and viewed from the data collection sources, the data used came from direct interviews with tellers and managers at BMT. The results of this study explain that BMT provides several savings products and financing products. To apply for financing, customers must first fill out a form and then complete the required files. In the implementation of musyarakah financing at BMT Dana Barokah Muntilan it is in accordance with Islamic sharia principles and the division of business with profit sharing, but the bank only as a provider of capital does not participate in conducting business activities. The profit-sharing determined by BMT Dana Barokah Muntilan is 2.5%, but negotiations are still possible.